1991
DOI: 10.1192/bjp.158.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Is Autism More Common Now than Ten Years Ago?

Abstract: A total population study of children, aged 13 years and under, suggested that there has been an apparent rise in the frequency of autistic disorder and autistic-like conditions (excluding Asperger's syndrome) in one area of western Sweden over the last ten years. The frequency was 4.0/100,000 in 1980, 7.5/10,000 in 1984 and 11.6/10,000 in 1988 in the city of Göteborg. Even though the prevalence rates refer to slightly different age cohorts, it was concluded that the apparent increase is in part due to better d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
1
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(146 citation statements)
references
References 18 publications
4
132
1
9
Order By: Relevance
“…The speech difficulties could be explained by severe hearing impairment, tracheostomy and cleft palate, and learning disability and autism also affected the ability to communicate. The rate of autism in the general population is about 1-2 in 1000 [Bryson et al, 1988;Gillberg et al, 1991;Gillberg and Wing, 1999;Wing and Potter, 2002]. Our data suggest that autism/atypical autism is much more common in CA than in the general population given that 40% of our comprehensively examined subjects met the criteria for autism/atypical autism.…”
Section: Prenatal Event Nmentioning
confidence: 72%
“…The speech difficulties could be explained by severe hearing impairment, tracheostomy and cleft palate, and learning disability and autism also affected the ability to communicate. The rate of autism in the general population is about 1-2 in 1000 [Bryson et al, 1988;Gillberg et al, 1991;Gillberg and Wing, 1999;Wing and Potter, 2002]. Our data suggest that autism/atypical autism is much more common in CA than in the general population given that 40% of our comprehensively examined subjects met the criteria for autism/atypical autism.…”
Section: Prenatal Event Nmentioning
confidence: 72%
“…Two epidemiological surveys of autism prevalence that applied robust case-ascertainment methods were conducted in western Sweden during the early and late years of the birth-cohort (37,38). The prevalence rates reported in those surveys (5.6 and 9.1 per 10,000, respectively) are similar to those in the national register, supporting the registry's representativeness.…”
Section: Birth-cohort Studymentioning
confidence: 73%
“…11 The same applies to the third approach, which compared rates estimated in repeat surveys in the same geographical area. 12 A fourth approach tested the hypothesis of a secular increase in comparing rates in successive birth cohorts surveyed with rigorously comparable methods, but no statistical difference in rates was found. 13 Finally, the fifth approach is represented by two recent incidence studies 14,15 which both showed increased incidence rates in the early 1990s.…”
mentioning
confidence: 99%